Android-Based Psychonurse App Management to Measure Nurse Job Satisfaction - Puput Mulyono; Singgih Purnomo (International Journal of Economics and Management Research, 2025)
In recent years, nurse job satisfaction has become a very important topic in the world of Health. This is because nurses' job satisfaction can affect the quality of health services provided to patients. However, the measurement of nurses' job satisfaction is still carried out manually and has not been effective. A system is needed that can measure nurses' job satisfaction effectively and efficiently. Android-based psychological test management to measure nurses' job satisfaction is one of the solutions that can be used to measure job satisfaction effectively and efficiently. Using an android-based application, nurses can fill out an online job satisfaction questionnaire and the results can be analyzed automatically. Thus, android-based psychological test management to measure nurses' job satisfaction can help improve the quality of health services. The urgency of research is to measure nurses' job satisfaction so that nurses' performance increases in serving patients. The original purpose of this research is to produce android-based mobile psychological test software where this software can be used as a medium to streamline and make it easier to measure nurses' job satisfaction. The method in this study is to collect data about psychological tests, through books starting from questions about statements to the search that will occur as a result of this application.